RADIOGRAPHY TECHNIQUE OF OS FEMUR DEXTRA IN CASE OF 1/3 DISTAL FRACTURE AT RADIOLOGY INSTALLATION OF EFARINA ETAHAM BERASTAGI HOSPITAL IN 2021 - Sihat Manisia Siboro; Saufa Taslima; Juni Sinarinta Purba; Awan Pelawi; Bambang Kustoyo; Dea Rahmayani Barus (PT. Radja Intercontinental Publishing, 2021)
A fracture is a break in the continuity of the epiphyseal plate or growth cartilage (Foris and Waseem, 2018). A fracture is a loss of bone continuity, either totally or partially, caused by trauma or physical exertion. This research was conducted to determine the characteristics of patients with femoral fractures due to traffic accidents at Efarina Etaham Berastagi Hospital in 2021. This study used a descriptive method. research is the entire population that follows the inclusion and exclusion criteria. The sample selection was carried out by the total sampling method. This research was conducted by looking at secondary data, namely medical records of patients with femoral fractures due to traffic accidents at Efarina Etaham Berastagi Hospital.